EVALUATION STUDY MANAGEMENT OF SOLID MEDICAL WASTE AT DR. H. SLAMET MARTODIRDJO HOSPITAL PAMEKASAN - Nazilatul Fadhoilah; Waluyo Jati; Darjati . (GEMA LINGKUNGAN KESEHATAN, 2013)
Results of the conducted initial survey found that there were some issues where medicalwaste containers were not in place and incineration of solid medical waste was not done withinthe usual 5 day period. This study was aimed at evaluating the management of solid medicalwaste at Dr. H. Siamet Martodirdjo hospital in Pamekasan.This study was designed as a descriptive study, conducted in February - June of 2013.Data were analyzed descriptively and to be discussed with reference to the KepMenKes NO.1204/Menkes/SK/X/2004 on Hospital Environmental Health Requirements.Results of this study indicated that solid medical waste at hospital of Dr. H. SiametMartodirdjo Pamekasan was generated from health care activities performed in the emergencyroom, leu and other units in the form of infectious materials and sharps. Largest amount ofsolid medical waste was produced usually on Monday at 50kg, while the smallest amountgenerated in any other day of the week wasapproximately 12kg. Evaluation on the solid medicalwaste management resulted in a score of 75.64% and considered as a non-compliance. Thesmallest percentage achieved in the assessment was 28.6% obtained by janitorial service andthe largest percentage was from the transportion as much as 90%.The study concluded that the management of solid medical waste in Pamekasan hospitalsis not complying to the desiqnated standards. The study suggested that Dr.H.SlametMartodirdjo Pamekasan hospital should make immediate corrections pertaining to medical solidwaste management and improvement of the janitorial service, the system, and a schedule thatis in compliance to the KepMenKes NO.1204/Menkes/SK/X/2004 on Hospital EnvironmentalHealth Requirements.Keywords: Solid medical waste, Hospital